Chemical Composition of the Essential Oils of Cymbopogon citratus (DC.) Stapf Cultivated in North of Brazil. - Andrade, Eloisa Helena A. (2009)
The essential oils obtained from blades, sheaths and rhizomes of Cymbopogon citratus were obtained by hydrodistillation and analyzed by GC-FID and GC-MS. The essential oils from aerial parts (blades and sheaths) from three other specimens also were studied. Neral and geranial were major in blades (30.1 % and 39.9 %, respectively), and sheats (27.8 % and 50.0 %, respectively). Rhizome oils showed a different chemical profile and was characterized by a high amount of selina-6-en-4-ol (27.8 %), followed by α-cadinol (8.2 %), neointermediol (7.2 %) and eudesma-7(11)-en-4-ol (5.3 %).